Health‐related quality of life among breast cancer survivors and noncancer controls over 10 years: Pink SWAN. Issue 10 (27th February 2020) - Avis, Nancy E.; Levine, Beverly; Goyal, Neha; Crawford, Sybil L.; Hess, Rachel; Colvin, Alicia; Bromberger, Joyce T.; Greendale, Gail A.
Abstract : Background: The goal of this study was to compare health‐related quality of life (HRQL) from diagnosis to 10 years postdiagnosis among breast cancer survivors (BCS) and women without cancer over the same period and to identify BCS subgroups exhibiting different HRQL trajectories. Methods: Our analysis included 141 BCS and 2086 controls from the Study of Women's Health Across the Nation (SWAN), a multiracial/ethnic cohort study of mid‐life women assessed approximately annually from 1995 to 2015. Pink SWAN participants reported no cancer at SWAN enrollment and developed (cases) or did not develop (controls) incident breast cancer after enrollment. We assessed HRQL with SF‐36 Mental Component Summary and Physical Component Summary scores. We modeled each as a function of case/control status, years since diagnosis, years since diagnosis squared, and the interaction terms between case/control status and the 2 time variables in linear models. We characterized heterogeneity in postdiagnosis HRQL of cases using group‐based trajectories. Results: BCS had significantly lower HRQL compared with controls at diagnosis and 1 year postdiagnosis. By 2 years, BCS and controls no longer differed significantly. Among BCS, 2 trajectory groups were identified for both scores. For the Mental Component Summary, 88.4% of BCS had consistently good and 11.6% had very low scores. For the Physical Component Summary, 73.9% had good scores, and 26.1% had consistently low scores. Prediagnosis perceived stress and current smoking were related to being in the low mental trajectory group, and a higher number of comorbidities was related to being in the low physical trajectory group. Conclusion: Although the majority of BCS have HRQL similar to non‐cancer controls after 2 years, subgroups of BCS continue to have low HRQL. Prediagnosis stress, comorbidities, and smoking are vulnerability factors for long‐term, low HRQL in BCS. Abstract : A longitudinal cohort of middle‐aged women reveals that the majority of breast cancer survivors have health‐related quality of life (HRQL) similar to noncancer controls after 2 years. However, subgroups of survivors continue to have low HRQL. Stress, comorbidities, and smoking prior to diagnosis are vulnerability factors for long‐term, low HRQL in breast cancer survivors.